Analisis Tindak Tutur Perlokusi dalam Film Kembang Api Karya Herwin Novianto - Alisia Nilam Sekar Ayu; Azyarni Anjani; Revalina Aulia Ramadhani; Aninda Feriska Putri; Sandy Aulia; Asep Purwo Yudi Utomo; Yusro Edy Nugroho (Student Scientific Creativity Journal, 2024)
Speech acts play an important role in conveying meaning through utterances. In these utterances, sometimes there are utterances that can cause effects called perlocutionary speech acts. Speech acts can occur in the world of cinema, especially in dialog between characters. As in the movie Kembang Api by Herwin Novianto, which tells about a series of life problems and suicide attempts packaged with the concept of timeloop. The interesting thing to study from the selection of this film is that the conditions experienced by the characters in the film are considered relevant to the current situation. This research aims to gain a deeper understanding of the use of perlocutionary speech acts in movies. Through this research, we can understand how perlocutionary speech acts are represented in the movie Kembang Api. This research uses descriptive qualitative method with pragmatics study. This research utilizes data in the form of perlocutionary speech acts, such as verbal, nonverbal, and verbal nonverbal. Data collection is done using listening and note-taking techniques. The data analysis technique in this research uses the flow model analysis technique. Based on the data and analysis, 75 perlocution data were found which were classified into verbal, nonverbal, and verbal nonverbal which were adjusted to the type. This research has implications in adding to the reader's repertoire of knowledge related to references to the delivery of polite criticism. The movie has potential in fields of science other than pragmatics such as psycholinguistics.